If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6j + 18 = 3j + -3 Reorder the terms: 18 + -6j = 3j + -3 Reorder the terms: 18 + -6j = -3 + 3j Solving 18 + -6j = -3 + 3j Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-3j' to each side of the equation. 18 + -6j + -3j = -3 + 3j + -3j Combine like terms: -6j + -3j = -9j 18 + -9j = -3 + 3j + -3j Combine like terms: 3j + -3j = 0 18 + -9j = -3 + 0 18 + -9j = -3 Add '-18' to each side of the equation. 18 + -18 + -9j = -3 + -18 Combine like terms: 18 + -18 = 0 0 + -9j = -3 + -18 -9j = -3 + -18 Combine like terms: -3 + -18 = -21 -9j = -21 Divide each side by '-9'. j = 2.333333333 Simplifying j = 2.333333333
| 8m^2-6=0 | | 17+x=130 | | (2x-7x^2+3x^3)=60 | | -3x-6=-2x-14 | | 13x+3=27-3x | | -x-2=15x | | .5x+1.5= | | 2x+6=134 | | x-22+3x=-29-3x-33 | | -64x^2+56x-12=0 | | 20(0.5882352941)+(-20)(1-0.5882352941)=x | | -7c+-2d= | | 20(0.58)+(-20)(1-0.58)=x | | 4h+3=9h+1 | | 4(2x+6)=54 | | -8a+5= | | 5x+4=2x+34 | | 10x-2x+62=10x+40 | | 20(0.59)+(-20)(1-0.59)=x | | 20p+(-20)(1-p)=(-15)p+30(1-p) | | 49+77+x=180 | | 49+77+x=90 | | 4/11P-7=1 | | 12y-7x=42 | | 18=j-14 | | 49.23x=200 | | 35+62+x=180 | | 81x=1 | | X-3/16= | | 8=n-51 | | 2(11+g)=10 | | 46+42+x=180 |